2012
DOI: 10.1136/archdischild-2012-302360
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth in a nationwide cohort of coeliac disease patients

Abstract: Background and objective Genetic factors alone cannot explain the risk of developing coeliac disease (CD). Children born in summer months are likely to be weaned and introduced to gluten during winter when viral infections are more frequent. Earlier studies on birth season and CD are limited in sample size and results are contradictory. Method Case-control study. We used biopsy reports from all 28 Swedish pathology departments to identify individuals with CD, defined as small intestinal villous atrophy (n=29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 27 publications
3
28
1
Order By: Relevance
“…The first study followed children up to 1997, and found summer to be associated with increased risk in children diagnosed before the age of 2 years 8. Lebwohl et al using Swedish pathology data showed a slightly increased risk in adults born during summer 9. Lewy et al reported increased CD risk in girls born during summer and in children diagnosed before 2 years of age but not in boys or in older children 10.…”
Section: Discussionmentioning
confidence: 99%
“…The first study followed children up to 1997, and found summer to be associated with increased risk in children diagnosed before the age of 2 years 8. Lebwohl et al using Swedish pathology data showed a slightly increased risk in adults born during summer 9. Lewy et al reported increased CD risk in girls born during summer and in children diagnosed before 2 years of age but not in boys or in older children 10.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence, however, is not clear. Some studies have found infections at the time of gluten introduction not to be associated with increased risk of CD [46,47] .…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…To date, there have been two published studies on the season of birth-CD association in North America [33], three in Northern Europe [13,16], and one in Israel [18].…”
Section: Introductionmentioning
confidence: 99%